2022
DOI: 10.3389/fphar.2022.1013485
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for and willingness to vaccinate with the COVID-19 vaccine booster dose in China

Abstract: Objective: The present study aims to assess the willingness to pay (WTP) for and willingness to vaccinate (WTV) with the Coronavirus (COVID-19) vaccine booster dose in China when the pandemic is under adequate control and the majority of the population is vaccinated. This study is also to identify significant factors associated with the WTP.Methods: This was a cross-sectional study on adults with no past or present COVID-19 infection. An online questionnaire was distributed to collect data on vaccination statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
(66 reference statements)
2
11
1
1
Order By: Relevance
“…We considered that the costs of vaccines could potentially act as a financial barrier to vaccination. This was particularly relevant for individuals who experience financial constraints or have a low household income [ 41 43 ]. Vaccination costs might increase disparities in access and raise concerns about equity and fairness.…”
Section: Discussionmentioning
confidence: 99%
“…We considered that the costs of vaccines could potentially act as a financial barrier to vaccination. This was particularly relevant for individuals who experience financial constraints or have a low household income [ 41 43 ]. Vaccination costs might increase disparities in access and raise concerns about equity and fairness.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals aged between 41–50, highly educated and earning more than 10 million IDR were willing to spend more for booster doses of COVID-19 vaccines. As mentioned earlier, WTP is influenced by factors such as age, education level, and monthly income, according to numerous studies [ 14 , 17 , 50 , 54 ]. More knowledge of the danger of COVID-19 can be ascribed to age and education, with lower levels of complacency linked to higher acceptance of vaccination [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this study, individuals older than 40 years showed higher WTP, which can be linked to higher perceived threats due to previous evidence showing that older individuals are at higher risk of developing severe disease with higher risk of mortality [ 57 , 58 ]. Thus, it is understandable to observe higher willing to receive the vaccine among individuals who are aware that COVID-19 can be a serious disease [ 54 , 59 ], with subsequent higher willingness to pay for the vaccine even if it is slightly more expensive. A higher WTP tendency increase was also previously linked with higher monthly income [ 17 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, the contingent valuation method (CVM) strives to elicit the maximum amount of money each person affected by a public health programme would be prepared to pay to reduce their risk of morbidity or death from a specific cause [34][35][36], e.g., COVID-19. For example, Zhou et al [37] employed CVM to assess willingness-to-pay (WTP) among 543 participants in China for the COVID-19 vaccine booster dose. Cerda and García [38] conducted a double-bounded dichotomous choice questionnaire survey among 531 participants to estimate the WTP for a COVID-19 vaccine in Chile.…”
Section: Model For Estimating the Total Present Value Of Human Life L...mentioning
confidence: 99%